Analisis Pengaruh Temperatur, Waktu, dan Kuat Arus Proses Elektroplating terhadap Kekuatan Tarik, Kekuatan Tekuk dan Kekerasan pada Baja Karbon Rendah - Rasyad, Abdul; Budiarto, Budiarto (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2018)
The researcher has analyzed the effect of temperature, time, and electrical current of electroplating process on tensile strength, bending strength and hardness of low carbon steel. The aim of this research is to know the effect of temperature, time, and electrical current as the parameters of electroplating process on tensile strength, bending strength and hardness of low carbon steel plate material treated using nickel and chrome coating materials. Coating process was operated with variations in temperature of 50 ° C, 55 ° C, 60 ° C; coating time of 5 minutes, 10 minutes, 15 minutes; and electrical currents of 4 A, 5 A, 6 A. Tensile strength and buckling tests were conducted using a versatile test machine (Universal Testing Machine) and hardness test with Vickers method. The tensile strength test results show that the higher temperature, time and electrical current during the coating process, give the greater of tensile strength value (from 307 N / m2 to 376 N /m2), as well as buckling strength testing.The smaller of buckling strength value from 11.5 kg / m2 to 7.5 kg / mm2. Hardness test results indicate a significant increase in the value of hardness in the temperature variation, time, and the electrical current coating, where the hardness value is from 89.3 HV to 100 HV.